2017
DOI: 10.1080/03630242.2017.1333076
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer prevention-related knowledge and attitudes among female undergraduate students from different ethnic groups within China, a survey-based study

Abstract: Questionnaires from 493 participants aged from 16 to 26 years were included in the final database. The seven ethnic groups included in the final analysis were Han, Korean, Mongolian, Uyghur, Tibetan, Hui, and Tujia. Compared to the Han Chinese, the members of the other six ethnic groups had lower cervical cancer knowledge levels. The knowledge scores of Mongolian and Korean students were significantly lower than those of the Han Chinese. The willingness to accept cervical cancer prevention efforts also differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…These above-mentioned rates were still much lower than those in Hong Kong Chinese women (80.8%) [12,13], suggesting that women's screening participation might be affected by distinct socioeconomic levels across developed and undeveloped regions. We then observed that the willingness to screen of female migrants remained stable in last 3 years, but tended to be in a relatively high level when compared to previous surveys targeted different female groups in other cities (ranged from 63.3% to 85.0%) [14][15][16][17]. Hence, identifying barriers to get female migrants screened is urgently in need to be involved in cervical cancer prevention network of Shenzhen city, and the target of health education work should be placed on translating attitude or belief into practice according to the health belief model [18].…”
Section: Discussionmentioning
confidence: 77%
“…These above-mentioned rates were still much lower than those in Hong Kong Chinese women (80.8%) [12,13], suggesting that women's screening participation might be affected by distinct socioeconomic levels across developed and undeveloped regions. We then observed that the willingness to screen of female migrants remained stable in last 3 years, but tended to be in a relatively high level when compared to previous surveys targeted different female groups in other cities (ranged from 63.3% to 85.0%) [14][15][16][17]. Hence, identifying barriers to get female migrants screened is urgently in need to be involved in cervical cancer prevention network of Shenzhen city, and the target of health education work should be placed on translating attitude or belief into practice according to the health belief model [18].…”
Section: Discussionmentioning
confidence: 77%
“… 22 , 23 Despite the numerous published studies focusing on HPV and vaccination in recent years, there are only a few studies focusing on awareness and attitudes toward HPV and vaccination among the women aged 20 to 35 years, considering that HPV prevalence is relatively higher in Mainland China. 24 - 27 …”
Section: Introductionmentioning
confidence: 99%
“…22,23 Despite the numerous published studies focusing on HPV and vaccination in recent years, there are only a few studies focusing on awareness and attitudes toward HPV and vaccination among the women aged 20 to 35 years, considering that HPV prevalence is relatively higher in Mainland China. [24][25][26][27] The purpose of this study was to examine the prevalence of HPV and the awareness and attitudes associated with HPV and vaccination among young women aged 20 to 35 years, who need to be protected by HPV vaccination and were of suitable vaccination age in Fujian Province, China, and to provide recommendations for the promotion of HPV vaccination in Mainland China in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Non-Han Chinese women are (on average) less educated, poorer, and are more likely to live in rural communities. 22 In addition, women of non-Han ethnicity are less knowledgeable regarding the benefits of cervical cancer screening, are more skeptical regarding cervical cancer screening, and are less likely to have been screened for cervical cancer. 22 , 23 The 3 previous studies conducted in China that have examined acceptability of self-collection studied only Han women.…”
Section: Discussionmentioning
confidence: 99%
“… 22 In addition, women of non-Han ethnicity are less knowledgeable regarding the benefits of cervical cancer screening, are more skeptical regarding cervical cancer screening, and are less likely to have been screened for cervical cancer. 22 , 23 The 3 previous studies conducted in China that have examined acceptability of self-collection studied only Han women. 16 – 18 In contrast, our study was performed with women predominantly of the Yi, Hui, and Dai ethnicities.…”
Section: Discussionmentioning
confidence: 99%